The relationship between premenstrual syndrome and type of temperament in high school students - Zahra Mohebbi Dehnavi; Marzie Torkmannejad Sabzevari; Sedighe Rastaghi; Mostafa Rad (Mashhad University of Medical Sciences, 2017)
Introduction: Premenstrual syndrome (PMS) is one of the most common psychosomatic disorders in women at reproductive age that affects their quality of life. Temperament modification can occur with changing in diet. Diet patterns also affect PMS. This study was performed with aim to evaluate the relationship between PMS and types of temperament in high school students. Methods: This descriptive-analytic study was performed on 200 high school students in Sabzevar during 2 months in 2016. Data collection tools included temperament standard questionnaire, temporary identification PMS questionnaire, Beck depression questionnaire, and PMS daily record form. The students who had severe depression according to the Beck Depression Inventory were excluded from the study, and the symptoms of this syndrome were collected in two consecutive menstrual cycles according to the premenstrual syndrome questionnaire. Data was analyzed by SPSS software (version 23) and Chi-square and Logistic regression test. P< 0.05 was considered significant. Results: 165 participants (82.5%) had PMS. Most of them (49%) had moderate temperament. The prevalence of mix temperaments of hot and wet, hot and dry, and hot was 38% in PMS participants. Logistic regression test showed no relationship between variety of single and mix temperaments and having or not having PMS (P>0.05). Conclusion: However, PMS incidence was observed in combined hot and wet, hot and dry temperaments; there is no relationship between PMS and temperaments. So, it is recommended to do further studies in all layer of society with greater sample size.